Development of an inhaled medication administration protocol for intensive care practice: an experience report - Asturian, Kathleen; Pilger, Diogo (JORNAL DE ASSISTÊNCIA FARMACÊUTICA E FARMACOECONOMIA, 2026)
Objectives: To describe the process of developing a protocol for administering bronchodilator therapy via metered-dose inhaler to patients undergoing mechanical ventilation (MV). Methods: This is a qualitative, descriptive study in the form of an experience report. The development process occurred in five stages: 1) literature review; 2) construct elaboration; 3) content and face validation; 4) methodological quality assessment; and 5) protocol publication. Results: In the first stage, 23 studies were selected. Data extracted from the review served as the basis for the protocol recommendations. In stage 2, four documents were used as methodological references for guideline and protocol development. Based on these documents, the main elements frequently cited were identified, and the first version of the protocol was drafted. The third stage consisted of two rounds of validation: the first involved assessment by four experts, and the second by healthcare professionals (n = 35). In both rounds, the validity index exceeded 0.95 (excellent). In stage 4, the protocol’s methodological quality was evaluated by three PhD professors using the Appraisal of Guidelines for Research & Evaluation II instrument. Six quality domains were assessed. Five domains achieved scores above 90%, and one domain scored 68.52%. In the final stage, the protocol was formatted and published. Conclusions: The developed protocol is expected to provide support and recommendations enabling healthcare professionals to correctly administer inhaled medications during MV.